2000
DOI: 10.1084/jem.191.3.529
|View full text |Cite
|
Sign up to set email alerts
|

The First α Helix of Interleukin (Il)-2 Folds as a Homotetramer, Acts as an Agonist of the IL-2 Receptor β Chain, and Induces Lymphokine-Activated Killer Cells

Abstract: Interleukin (IL)-2 interacts with two types of functional receptors (IL-2Rαβγ and IL-2Rβγ) and acts on a broad range of target cells involved in inflammatory reactions and immune responses. For the first time, we show that a chemically synthesized fragment of the IL-2 sequence can fold into a molecule mimicking the quaternary structure of a hemopoietin. Indeed, peptide p1–30 (containing amino acids 1–30, covering the entire α helix A of IL-2) spontaneously folds into an α-helical homotetramer and stimulates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 37 publications
(45 reference statements)
2
23
1
Order By: Relevance
“…This region encompasses an amino acid residue (D34) within the ␣ helix A that is critical for the CD122 binding of IL-2 (10). In addition, the peptide encompassing ␣ helix A of human IL-2, termed p1-30, acts as an agonist through CD122 (11). These lines of evidence establish the neutralizing potential of the anti-IL-2 mAb.…”
Section: Il-2 In Vivo Activities and Antitumor Efficacymentioning
confidence: 94%
“…This region encompasses an amino acid residue (D34) within the ␣ helix A that is critical for the CD122 binding of IL-2 (10). In addition, the peptide encompassing ␣ helix A of human IL-2, termed p1-30, acts as an agonist through CD122 (11). These lines of evidence establish the neutralizing potential of the anti-IL-2 mAb.…”
Section: Il-2 In Vivo Activities and Antitumor Efficacymentioning
confidence: 94%
“…As previously demonstrated, p1-30 induces the proliferation of cell lines expressing the human IL-2R␤-chain (24). was observed between p1-30 and IL-2 because the proliferative response obtained with the combination of p1-30 ϩ IL-2 was much greater than the sum of each individual response.…”
Section: Peptide P1-30 Acts In Synergy With Il-2 -4 -9 or -15mentioning
confidence: 53%
“…In human PBMC, p1-30 induces lymphokine-activated killer (LAK) cells and leads to the production of IFN-␥. We have also suggested that p1-30 has therapeutic potential (24).…”
mentioning
confidence: 88%
See 2 more Smart Citations